Hypo- and normothermic perfusion of the liver: Which way to go?. Issue 2 (April 2017) - Selten, Jasmijn; Schlegel, Andrea; de Jonge, Jeroen; Dutkowski, Philipp
Abstract: The demand of donor livers for transplantation exceeds the supply. In an attempt to maximize the number of potentially usable donor livers, several centers are exploring the role of machine perfusion. This review provides an update on machine perfusion strategies and basic concepts, based on current clinical issues, and discuss challenges, including currently used biomarkers for assessing the quality and viability of perfused organs. The potential benefits of machine perfusion on immunogenicity and the consequences on post-operative immunosuppression management are discussed.